ROIC (Return on Invested Capital), as a metric of financial efficiency - Gaytán Cortés, Juan (Mercados y Negocios, 2025)
Organisations generally invest capital in acquiring industrial warehouses, machinery, research laboratories, offices, and other similar long-lived assets, as well as hiring personnel to manage, oversee the production process, and make purchases of raw materials, while also extending credit to their customers. Shareholders can provide financial resources through capital exhibitions, the generation and retention of profits or through the contracting of debt.